Analysis of Cafe Customer Satisfaction from a Maqasid Syariah Perspective - Maksum Maksum; Irvan Arisandi; Muktirrahman Muktirrahman; Nurul Huda (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2026)
Backgound. Islamic-based cafes face dual responsibilities: achieving business success while implementing Islamic economic principles. Customer satisfaction in Islamic perspective encompasses not only material fulfillment but also spiritual dimensions based on maqasid sharia principles (hifz ad-din, an-nafs, al-'aql, an-nasl, al-mal). However, conventional satisfaction measurements often neglect these spiritual-ethical aspects, creating a gap in understanding holistic customer satisfaction in Islamic business contexts. Aim. This study examines the influence of service quality, price, and cafe atmosphere on customer satisfaction with purchase decision as a mediating variable at Kancakona Kopi Sumenep, integrating maqasid sharia perspective to provide comprehensive understanding of customer satisfaction in islamic cafe business. Methods. Quantitative research with 96 respondents analyzed using SEM-PLS SmartPLS 3.0 to test direct, indirect effects and mediation roles. Results. Price has the strongest influence on both purchase decisions and customer satisfaction, demonstrating successful implementation of Islamic pricing justice (qimah ᾱdilah) and bilateral wealth protection (hifz al-mal). Cafe atmosphere significantly affects purchase decisions, reflecting its role as a conducive Islamic environment (bi'ah solihah) supporting protection of intellect and soul (hifz al-'aql and hifz an-nafs). Service quality directly affects customer satisfaction, indicating that excellence of service (ihsan) manifests in post-consumption evaluation. Purchase decision partially mediates the relationships between price and satisfaction as well as atmosphere and satisfaction. From the maqasid sharia perspective, fair pricing and conducive atmosphere successfully transform into customer satisfaction through cognitive-evaluative processes embedded in purchase decisions, yet service excellence operates through direct achievement of holistic wellbeing (maslahah).